885 Safe schools project, South Africa. (1st September 2016) - Mtambeka, PP; As, AB Van; Mavengere, CA; Niekerk, A Van; Elliot, G; Mcinerney, R
Abstract : Background: The World health Organisation indicates that child pedestrian injuries are highest in African countries with a continental mortality rate that is twice the global world (WHO 2011). In South Africa it is noted that the majority of children walk to and from school, placing them at particular risk to road traffic crashes resulting in injury, disability or death(Stats SA 2013) Child pedestrians are particular vulnerable to road crashes due to their physical and cognitive limitations. Methods: The Safe School project aimed to reduce child pedestrian injuries and deaths in South Africa by introducing the iRAP star rating concept, which provides tools and training to help countries make roads safe by inspecting high-risk roads and developing star ratings for those roads, with the ultimate goal of eliminating one- and two-star rated roads from the world's road network. 3 primary schools were selected in South Africa where intervention took place and 1 school served as a control for monitoring and evaluation purposes. Results: The pilot project has developed an innovative model combining education for the school children, training for teachers and advocacy action to catalyse the introduction of safe road infrastructure. It has also enabled creation of a multi-stakeholder partnership and further contributed to development of educational tool kit by Takalani Sesame (Sesame Street). The project has been successful in one of its primary objectives to encourage the government to ensure sustained investments for safer roads thorough collaboration with City of Cape Town road engineers. Conclusion: The project has been effective as a model for catalysing sustainable investment in interventions aimed to improve road safety for school children. This model has the potential to be replicated on a wider basis across other schools in South Africa and other countries. With its outcomes and potential long term impact, it has already made valuable contribution to the Decade of Action for Road Safety and has the potential to do so.